Genome-wide meta-analysis identifies novel gender specific loci associated with thyroid antibodies level in Croatians - Matana, Antonela; Popović, Marijana; Boutin, Thibaud; Torlak, Vesela; Brdar, Dubravka; Gunjača, Ivana; Kolčić, Ivana; Boraska Perica, Vesna; Punda, Ante; Polašek, Ozren; Hayward, Caroline; Barbalić, Maja; et al. (Genomics (San Diego, Calif.), 2019)
Autoimmune thyroid diseases (AITD) are multifactorial endocrine diseases most frequently accompanied by Tg and TPO autoantibodies. Both antibodies have a higher prevalence in females and act under a strong genetic influence. To identify novel variants underlying thyroid antibody levels, we performed GWAS meta-analysis on the plasma levels of TgAb and TPOAb in three Croatian cohorts, as well as gender specific GWAS and a bivariate analysis. No significant association was detected with the level of TgAb and TPOAb in the meta-analysis of GWAS or bivariate results for all individuals. The bivariate analysis in females only revealed a genome-wide significant association for the locus near GRIN3A (rs4457391, P = 7.76 × 10−9). The same locus had borderline association with TPOAb levels in females (rs1935377, P = 8.58 × 10−8). In conclusion, we identified a novel gender specific locus associated with TgAb and TPOAb levels. Our findings provide a novel insight into genetic and gender differences associated with thyroid antibodies. •GRIN3A locus was associated with thyroid antibodies levels in females.•GRIN3A locus was marginally associated with TPOAb levels in females.•DLL1 locus was marginally associated with TgAb levels in females.•Gender specificity of genetic influences on thyroid antibody level was confirmed.